1985
DOI: 10.1136/gut.26.6.570
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic Escherichia coli enteritis: evaluation of the gnotobiotic piglet as a model of human infection.

Abstract: SUMMARY The pathogenicity of classical enteropathogenic Escherichia coli strains of human origin was investigated in gnotobiotic piglets. One to two day old piglets in groups of four were infected perorally with approximately 10 colony forming units of one of eight enteropathogenic E coli strains or a non-pathogenic control strain. Animals were necropsied 24 or 48 hours after infection and their intestines were subjected to histological examination, quantitative bacterial culture and estimation of lactase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
73
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 26 publications
8
73
0
Order By: Relevance
“…Elongated microvilli adjacent to the attachment sites have previously been reported in pigs [6], rabbits [4] and chicks [5]. The developmental mechanism of AE lesions in these animals also seemed to be consistent with that in humans.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Elongated microvilli adjacent to the attachment sites have previously been reported in pigs [6], rabbits [4] and chicks [5]. The developmental mechanism of AE lesions in these animals also seemed to be consistent with that in humans.…”
supporting
confidence: 60%
“…It colonizes the intestinal tract and adheres intimately to the enterocytes, resulting in the effacement of microvilli and formation of pedestals [3]. Although there have been many reports on attaching and effacing (AE) lesions in several species with AEEC infection [4][5][6], only one report dealt with the developmental process of AE lesions [2]. We investigated AE lesions on the enterocytes in a one-month-old calf and a piglet, and we found the developmental process of AE lesions in the calf was different from that in the piglet.…”
mentioning
confidence: 99%
“…(68). Others have demonstrated that EPEC induces A/E lesions in other hosts, such as rabbits and piglets (41,50,67), and that REPEC colonizes the mouse intestinal epithelium as well (49). In contrast, Frankel et al reported that no EPEC colonies could be cultured from the intestine of Swiss NIH mice at 15 days postinfection (21).…”
Section: Discussionmentioning
confidence: 99%
“…In these early studies, no other signs of ASMscience.org/MicrobiolSpectrumdisease were reported. As was found in human infections, histologic abnormalities were detected in the cecum and colon, and primarily consisted of destruction of the mucosal brush border and inflammation (51). These first investigations recognized that E. coli O157:H7 caused intestinal lesions that were morphologically similar to those previously described for EPEC (52), and thus EHEC was considered a member of the same pathotype group (53).…”
Section: Historical Perspective On Animal Models Of Ehec-mediated Dismentioning
confidence: 75%